Material ethics of value Max Scheler and Nicolai Hartmann - Kelly, Eugene 1941-; SpringerLink (Online service). (Dordrecht New York Springer, 2011)
Max Scheler and Nicolai Hartmann developed ethics upon a phenomenological basis. This volume demonstrates that their contributions to a material ethics of value are complementary: by supplementing the work of one with that of the other, we obtain a comprehensive and defensible axiological and moral theory. By "phenomenology," we refer to an intuitive procedure that attempts to describe thematically the insights into essences, or the meaning-elements of judgments, that underlie and make possible our conscious awareness of a world and the evaluative judgments we make of the objects and persons we encounter in the world
1 The idea of material value-ethics 2 The phenomenology of value 3 The orientation of human beings toward value 4 Values and moral values 5 Action theory and the problem of motivation 6 Goodness and moral obligation 7 The concept of virtue and its foundations 8 Virtue ethics 9 The phenomenology of the person 10 Ethical personalism Bibliography Index
Includes bibliographical references (pages 239-246) and index
Electronic reproduction
Keywords: Scheler, Max -- 1874-1928.; Hartmann, Nicolai -- 1882-1950.; Ethics